High frequency surface wave radar signal modeling and processing - Wang, William Hup Joo. (2010)
The use of radar has grown tremendously from its original use in the military, to its modern use in the air traffic control system. Different types of radar have been developed over the years to meet the needs of various applications and systems. High Frequency (HF) radars, also known as the over-the-horizon radars, are widely used in maritime surveillance, maritime safety and oceanography due to their ability to detect targets that are over-the-horizon. The intrinsic properties of a HF signal enable the radio frequency (RF) signal to either use the atmosphere to propagate also known as sky wave propagation and hence Sky Wave Radar or another which hug along the earth surface also know as surface wave propagation and hence called Surface Wave Radar. The focus of this project will be on the High Frequency Surface Wave Radar (HFSWR). High Frequency Surface Wave Radar (HFSWR) operates in the High-Frequency bands (3-30 MHz) in the electromagnetic spectrum and can typically covers ranges up to 250 to 300 km. The advantage of using the HFSWR system is that it can operate independently of the ionosphere, thus eliminating significant aspect of variations and complexity. The setting up of a HFSWR site requires extensive works and preparation. Thus, it will be an advantage if the simulation of the set-up as well as the system can be done prior to the actual work being done. The goal of this project is to develop a MATLAB simulation toolbox for the study of various HFSWR related signal modeling and processing.